Life-Cycle Patterns of Interest Rate Markups in Small Firm Finance - Moshe Kim; Eirik Gaard Kristiansen; Bent Vale (Norges Bank, 2007)
We derive empirical implications from a stylized theoretical model of bankborrower relationships. Banks' interest rate markups are predicted to follow a life-cycle pattern over the borrowing firms' age. Due to endogenous bank monitoring by competing banks, borrowing firms initially face a low markup, thereafter an increasing markup due to informatonal lock-in until it falls for older firms when lock-in is resolved. By applying a large sample of small unlisted firms and a new measure of asymmetric information, we find that firms with significant asymmetric information problems have a more pronounced life-cycle pattern of interest rate markups. Additionally, we examine the effects of concentrated banking markets on interest markups. Results indicate that markups are mainly driven by asymmetric information problems and not by concentration. However, we find weak evidence that bank market concentration matters for old firms.
hdl:11250/2498273
Keywords: G21; L15; 330